The craft of information visualization readings and reflections - Bederson, Benjamin. (Morgan Kaufmann, 2003)
The overall goal of research in Human-Computer Interaction (HCI) is to improve the experience of people using computers, making that experience more efficient and intuitive. The University of Maryland's Human-Computer Interaction Lab (HCIL) has repeatedly found that the most effective way to improve the human-computer experience is through the visual sense. Information visualization, the branch of research that studies the human-computer visual interface, has become a major theme during the past 10 years at HCIL. This book collects for the first time 38 of the key papers on information visualization.